Career Development Influences of Employees Working in Haiti’s Agricultural Extension and Advisory Services - Bertrhude Albert; Grady Roberts; Amy Harder (Journal of International Agricultural and Extension Education, 2017)
Agricultural Extension and Advisory Services (EAS) provide vital services to individuals within the developing world. Extension personnel are at the heart of extension services because they are the ones who provide essential support, training, and skills to farmers in rural areas. The capacity of extension personnel, therefore, is an essential component of having a robust AET system. The purpose of this research was to explore and describe influences on career development among extension personnel in Haiti. To achieve this purpose, the set objectives of the research were: (a) describe career development influences in a government run extension agency in Haiti; (b) describe career development influences in a private run extension agency in Haiti; (c) describe career development influences in a grassroots extension agency in Haiti; and (d) compare and contrast career development influences in these agencies. Qualitative data from across the agencies showed common positive influences of: (a) educational background, (b) inservice training, (c) intrinsic motivation, and (d) extrinsic motivation. The common negative influences included: (a) lack of resources and (b) environmental hindrances.
Keywords: Haiti; career development; extension education; Caribbean; advisory services